Understanding human agency - Mayr, Erasmus (Oxford, New York Oxford University Press, 2011)
How can we be active agents when processes in the world are explicable by the laws of natural science? Erasmus Mayr explores this deep-running tension in our self-understanding and develops a new agent-causal solution to the conflict. He argues that actions explained by aims and reasons are compatible with a scientific view of the universe.
Includes bibliographical references and index.
Electronic reproduction.
Keywords: Act (Philosophy); Agent (Philosophy); Electronic books